2019
DOI: 10.3390/v11070632
|View full text |Cite
|
Sign up to set email alerts
|

Potential Viroporin Candidates From Pathogenic Viruses Using Bacteria-Based Bioassays

Abstract: Viroporins are a family of small hydrophobic proteins found in many enveloped viruses that are capable of ion transport. Building upon the ability to inhibit influenza by blocking its archetypical M2 H+ channel, as a family, viroporins may represent a viable target to curb viral infectivity. To this end, using three bacterial assays we analyzed six small hydrophobic proteins from biomedically important viruses as potential viroporin candidates. Our results indicate that Eastern equine encephalitis virus 6k, We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 58 publications
4
26
0
1
Order By: Relevance
“…This system ensures targeting of the protein to the inner bacterial membrane. While this membrane may not be identical to the eukaryotic Golgi-ER compartment where 3a is thought to reside [ 55 , 56 ], it was used to express and examine many other viral ion channels successfully [ 35 , 53 , 55 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This system ensures targeting of the protein to the inner bacterial membrane. While this membrane may not be identical to the eukaryotic Golgi-ER compartment where 3a is thought to reside [ 55 , 56 ], it was used to express and examine many other viral ion channels successfully [ 35 , 53 , 55 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Future electrophysiological studies will be needed to assess the detailed inhibitory mechanisms of each chemical. In addition, in vitro and in vivo studies will be required to establish the anti-viral activity of the different blockers considering the intracellular localization of the protein and the ability of individual hits to access it [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure proper membrane reconstitution, we used the MBP Fusion and Purification System (New England BioLabs, Ipswich, MA) in which the E protein was fused to the carboxy terminus of the maltose-binding protein. This system has been used to express and study numerous other viral ion channels successfully (2326). Finally, we have recently shown that SARS-CoV-2 E protein is also expressed in functional form utilizing this construct (16).…”
Section: Resultsmentioning
confidence: 99%
“…These bacteria are incapable of growth unless the media is supplemented by K + (27). However, when a channel capable of K + transport is heterologously expressed, the bacteria can thrive even in low K + media (25, 26). Hence, in this instance, the viral channel positively impacts the bacteria, and channel blockers result in growth retardation.…”
Section: Resultsmentioning
confidence: 99%